Theory of lift : introductory computational aerodynamics with MATLAB R/OCTAVE - McBain, G. D. (Geordie G.) (Chichester, West Sussex, UK : Hoboken, NJ : Wiley, 2012)
"Accessible introduction to aerodynamics using a unique computational approach based on widely available MATLAB software tools. Based on the author's years of experience teaching aerodynamics to students, he has developed an approach combining the use of widely available MATLAB commercial code (also compatible with Octave GNU open source code) with clear narrative explanations of the concepts that simplifies the understanding of aerodynamics without sacrificing the mathematical underpinnings or leaving the reader overwhelmed with complex formulas. The ability of the reader to download and run the code examples makes this an ideal self-learning tool, as well as a valuable course text. The choice of compatible MATLAB/Octave code ensures anyone can run the examples - either using open-source GNU Octave software as many consultancies and small firms do, or using the MATLAB commercial application (including the student edition) which is used widely in industry and is almost ubiquitous in academia. The code has been carefully compiled and checked for compatibility with both applications"--
"Provides a clear introduction to aerodynamics based on a line and panel methods"--
Front Matter -- Plane Ideal Aerodynamics. Preliminary Notions -- Plane Ideal Flow -- Circulation and Lift -- Conformal Mapping -- Flat Plate Aerodynamics -- Thin Wing Sections -- Lumped Vortex Elements -- Panel Methods for Plane Flow -- Three-Dimensional Ideal Aerodynamics. Finite Wings and Three-Dimensional Flow -- Vorticity and Vortices -- Lifting Line Theory -- Nonelliptic Lift Loading -- Lumped Horseshoe Elements -- The Vortex Lattice Method -- Nonideal Flow in Aerodynamics. Viscous Flow -- Boundary Layer Equations -- Laminar Boundary Layers -- Compressibility -- Linearized Compressible Flow -- Appendix A: Notes on Octave Programming -- Glossary -- Nomenclature -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: MATLAB; MATLAB; Lift (Aerodynamics) -- Mathematical models; Aerodynamics -- Data processing; TECHNOLOGY & ENGINEERING -- Aeronautics & Astronautics; Aerodynamics -- Data processing; Lift (Aerodynamics) -- Mathematical models; Electronic books